ANALYSIS OF HADITH ABOUT THE ESSENCE, OBLIGATIONS, AND ETHICS OF STUDENTS IN ISLAMIC EDUCATION: Analisis Hadis Tentang Hakikat, Kewajiban, Dan Etika Siswa Dalam Pendidikan Islam - Maslani; Khoirunnisa Alfadhilla; Meisya Nur Azizah; Risma Nurlela; Yesi Martaleni; Tatang Muh Nasir (Piwulang: Jurnal Pendidikan Agama Islam, 2025)
Students in Islam have an important role as seekers of knowledge and moral and spiritual shapers. This research aims to analyze the hadith about the nature, obligations, and ethics of students in pursuing knowledge. Using qualitative methods with a literature approach and descriptive analysis, this study found that students are required to maintain straight intentions, respect teachers, andhave a humble attitude and seriousness in learning. The hadiths studied affirm that seeking knowledge is the duty of every Muslim, which must be done with good intentions and the right ethics. This finding has implications for the Islamic education system in shaping the character of students who have noble character and are responsible for the knowledge obtained. By understanding the role and ethics in pursuing knowledge, students not only gain knowledge but also blessings in their lives